Theory of change supporting transitions from emergency cash transfers to rebuilding livelihoods - Hauser, Michael; Philip, Serene; Mugonya, John (International Food Policy Research Institute, 2021)
Safety nets protect vulnerable households when their livelihoods are deteriorating. Safety nets are offered to people through different instruments. Traditional asset programs transfer material goods, including farm implements and livestock if participants are farmers. Food and cash transfers are offered to people who lack access and are therefore at risk of selling-off productive assets during acute emergencies and chronic crises. Emergency cash transfers, in particular, have become more common over the past three decades.